Di Antara Dua Identitas: Proses Integrasi Keagamaan Komunitas Sikh dan Hindu di Tengah Status Pengakuan Agama di Medan - Danish ara Salsa; Irwansyah Irwansyah (Jurnal Pendidikan, Sains Sosial, dan Agama, 2026)
This study examines the process of religious integration between the Sikh and Hindu communities in Medan within the context of differing religious recognition statuses in Indonesia. Both communities are part of the Indian diaspora and share close ethnic, cultural, and migratory backgrounds; however, they occupy different positions within the state's religious recognition system, where Hinduism is officially recognized while Sikhism has not received formal recognition. This places the Sikh community between two identities: maintaining their Sikh religious identity while navigating administrative systems that favor officially recognized religions. A qualitative approach was employed through observation, in-depth interviews, and document analysis. The findings indicate that religious integration is shaped by shared ethnic and cultural backgrounds, kinship ties, and social interactions across various communal and religious activities, where differences in recognition status influence integration patterns, while religious practices continue to preserve Sikh identity through traditions, worship, and the gurdwara as the center of religious activity. Keywords: religious integration, Sikh community, Hindu, religious recognition status.